Conocimientos sobre problemas gastrointestinales en madres de niños menores de 5 años en el Centro de Salud N° 2 Hugo Guillermo González, Loja - Timbe Patiño, Jhuliana Elizabeth (2019)
Gastrointestinal problems are the second cause of death in children under five years old, these are caused by different factors, mainly by bacteria, viruses, parasites, fecal-oral contamination, deficiency of the sanitary infrastructure, lack of hygiene and bad habits. Therefore, it is important to know the relevant aspects of these types of problems, as well as the definition, prevention, signs and symptoms. Therefore, the objective of this research was to determine the knowledge that mothers with children under five years of age with gastrointestinal problems have at the Hugo Guillermo González Health Center No. 2 in the city of Loja, socio-demographically characterize the target population of studied and identified the knowledge that mothers have about gastrointestinal problems. The study was descriptive, involving 88 mothers with children under five years of age, who went to this health house, in the period between October 2018 and May 2019; Data were taken through the survey applied to mothers in the waiting room. This questionnaire had closed questions that correspond to the objectives of the investigation. The data were analyzed whose results correspond to; the majority of mothers who go to Health Center No. 2 Hugo Guillermo González have knowledge of 71.6% and 28.4% are unaware of it. KEY WORDS: Knowledge / mothers / children / gastrointestinal problems.